Changes in body weight, skeletal muscle and adipose tissue after gastrectomy: a comparison between proximal gastrectomy and total gastrectomy. Issue 1 (31st January 2019) - Asaoka, Raito; Irino, Tomoyuki; Makuuchi, Rie; Tanizawa, Yutaka; Bando, Etsuro; Kawamura, Taiichi; Terashima, Masanori
Abstract : Background: Proximal gastrectomy (PG) offers a well‐preserved digestive function after surgery, which may result in a better nutritional outcome in comparison to total gastrectomy (TG). The aim of this study was to clarify the advantage of PG over TG by evaluating the longitudinal changes in body weight (BW) and body composition after surgery. Methods: A total of 112 patients undergoing PG with a reconstruction preserving food passage through the duodenum ( n = 39) or TG with a reconstruction bypassing the duodenum ( n = 73) for clinical stage IA gastric cancer were included. Changes in BW, psoas muscle and subcutaneous (SAT) and visceral adipose tissue were assessed before surgery, and at 1 and 3 years after surgery and were compared between the two groups. Results: BW and SAT decreased significantly in both groups, but the rate of reduction was significantly lower in the PG group ( P < 0.001 and P < 0.001, respectively). There were no significant differences between the groups with regard to skeletal muscle or visceral adipose tissue ( P = 0.110 and 0.710, respectively), although they both significantly decreased throughout the course of the study. Conclusions: The losses of BW and SAT were significantly smaller in the PG group. PG may be superior to TG in preserving BW and SAT in patients with clinical stage IA gastric cancer. Abstract : The aim of this study was to clarify the advantage of proximal gastrectomy over total gastrectomy from a nutritional point of view. We analyse the changes in body weight and body composition after gastrectomy using a repeated measures analysis of variance.